Here Today, Gone Tomorrow - Three Common Mistakes Courts Make When Police Lose or Destroy Evidence with Apparent Exculpatory - Bawden, Elizabeth A. (2000)
Part I of this Article examines the first question, what does it mean for evidence to have apparent exculpatory value? Part II of this Article answers the second question, when does Youngblood's bad faith requirement apply in failure to preserve evidence cases? Part III then seeks to determine the substance of Youngblood's bad faith requirement and identify the best approach to defining it. Ultimately, this Article argues that there are three common mistakes that courts make when applying Trombetta and Youngblood